2015
DOI: 10.1007/978-3-319-19324-3_25
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to the Rule-Base Evidential Reasoning with Application

Abstract: Abstract. In this paper, a new approach to the rule-base evidential reasoning (RBER) based on a new formulation of fuzzy rules is presented. We have shown that the traditional fuzzy logic rules lose an important information when dealing with the intersecting fuzzy classes, e.g., such as Low and Medium, and this property may lead to the controversial results. In the framework of our approach, an information of the values of all membership functions representing the intersecting (competing) fuzzy classes is pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This is not surprising since the DST acts as a generalizing theory for a number of other well-known theories that model uncertainties. It is known that the probability and possibility theories are in some sense the asymptotic cases of the DST; in [15,22], we have shown that the DST is the useful generalization of the A − IFS, as well as of its intervalvalued extension; in [23], we have proved that the same is true in relation to the hesitant and interval-valued hesitant fuzzy sets; in [24], we have introduced the DST extension of the rule-base evidential reasoning in the intuitionistic fuzzy setting, which was used in [25] for the type 2 diabetes diagnostic; in [26], we have used the DST extension of the A − IFS in the generalization of the TOPSIS method. There is such a strong link between rough set theory and the DST that it is difficult to find a more general theory among them [27].…”
Section: Propositionsmentioning
confidence: 99%
“…This is not surprising since the DST acts as a generalizing theory for a number of other well-known theories that model uncertainties. It is known that the probability and possibility theories are in some sense the asymptotic cases of the DST; in [15,22], we have shown that the DST is the useful generalization of the A − IFS, as well as of its intervalvalued extension; in [23], we have proved that the same is true in relation to the hesitant and interval-valued hesitant fuzzy sets; in [24], we have introduced the DST extension of the rule-base evidential reasoning in the intuitionistic fuzzy setting, which was used in [25] for the type 2 diabetes diagnostic; in [26], we have used the DST extension of the A − IFS in the generalization of the TOPSIS method. There is such a strong link between rough set theory and the DST that it is difficult to find a more general theory among them [27].…”
Section: Propositionsmentioning
confidence: 99%
“…In [61], we presented the DST generalization of the rule-base evidential reasoning in the A − IF S environment. This approach we used in [62] for the type 2 diabetes diagnostic. We used the DST extension of the A − IF S to generalize the T OP SIS method in [7].…”
Section: The Studies Of the Dst Extension Of The A − If S Number Introduction Of A New Mathematical Object Belief-plausibility Numbermentioning
confidence: 99%